Employee Performance: Analysis Intuitive Leadership, Mentoring and Work Life Balance - Satriyanto, Muhammad Dwi; Natu Prihanto, Y. Johny; Sjarifudin, Didin; Sulistyo, Suryo; Dinarwati, Sri (Greenation Publisher & Yayasan Global Research National, 2023)
The purpose of this paper is to provide a view of various literature that already exists in the research results so as to contribute to the field of human resources. This paper uses qualitative methods by collecting literature related to the results or findings of papers within a period of ten years and given answers in the form of perceptions from these researchers as a form of contribution in the field of human resources. In general, from the variety found in this paper with the use of variables, results are found in various papers and research objects, but if it is made in all where the variables in one paper are not found existing literature from various journals. Furthermore, intuitive leadership variables have not been found specifically with variables that exist in the findings of papers in various journals.